2015
DOI: 10.1186/s12967-015-0499-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinduction and proliferation of bone-marrow stromal cells in three-dimensional poly (ε-caprolactone)/ hydroxyapatite/collagen scaffolds

Abstract: BackgroundOsteoinduction and proliferation of bone-marrow stromal cells (BMSCs) in three-dimensional (3D) poly(ε-caprolactone) (PCL) scaffolds have not been studied throughly and are technically challenging. This study aimed to optimize nanocomposites of 3D PCL scaffolds to provide superior adhesion, proliferation and differentiation environment for BMSCs in this scenario.MethodsBMSCs were isolated and cultured in a novel 3D tissue culture poly(ε-caprolactone) (PCL) scaffold coated with poly-lysine, hydroxyapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 52 publications
4
55
0
Order By: Relevance
“…Prior to imaging, the cells were fixed with 2.5% glutaraldehyde and samples were dehydrated in a graded ethanol series and sputter-coated with gold for 15–20 s. All samples were analyzed at 15 kV [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Prior to imaging, the cells were fixed with 2.5% glutaraldehyde and samples were dehydrated in a graded ethanol series and sputter-coated with gold for 15–20 s. All samples were analyzed at 15 kV [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Human thrombin, glutaraldehyde cross-linking agent, potassium chloride (KCl), potassium ferrocyanide (K 4 …”
Section: Materials and Apparatusmentioning
confidence: 99%
“…Synthetic HA has been extensively applied in biomedical implants [1,2], bone tissue engineering [3,4], drug delivery [5], and stem cell researches [6] owing to its excellent biocompatibility, bioactivity, porous structure and multi-adsorbing sites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies have shown the importance of collagen architecture for chondrocyte cell adhesion and migration e.g. in development of porous bioresorbable collagen beads and/or scaffolds (Tebb et al, 2006;Wardale et al, 2015) and for scaffolds intended for bone regeneration (Wang et al, 2015;Xia et al, 2014). Furthermore, in vivo studies have shown that in decellularized tissues the signaling properties of their residual ECM consisting of e.g.…”
Section: Discussionmentioning
confidence: 99%